Analisis Dampak Transformasi Sistem Pendidikan terhadap Penanaman Panca Jiwa Pondok Pesantren Kepada Santri di PP MMS Al Amin Bojonegoro - Habibi, Ibnu (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Modernization in world missionize and education of Islamic contemporary, do not only altering bases of sosio-kultural and knowledge of eye santri, but also induce at Islamic people as a whole. Equally culture of pesantren always experience of change process as according to its supporter society dynamics. Therefore big changes done/conducted by kyai to institutes of pesantren these days is not represent crosslegged alternative choice of road;street, but represent natural by life values accumulation of pesantren as long as history, without leaving ruh (typical tradition) of him. Maisonette of Pesantren in inculcating soul/ head pentameter need open also flexible and to demand and growth of world, but remain to provide filter so that his fade-proof elementary value (Islam teaching). In meaning, maisonette of pesantren do not only external mentransformasi of just him (target, curriculum, method, management system and management of pesantren) but needing wisely depth mentransformasi also (maisonette soul/head values of pesantren). This type of research is a qualitative descriptive research approach used is a philosophical, psychological, and pedagogical approach. The data sources of this study consisted of Kyai or Director, Principals, students, boarding supervisors, teachers/teachers and students/students. Data collection methods used are observation, interviews, and documentation. This study aims to determine how the Impact of Education System Transformation on the Planting of the Five Souls of Islamic Boarding Schools to Santri in PP MBS Al Amin Bojonegoro.